A survey on prevalence of oxyuriasis among primary school students in samut prakan province - Choosak Nithikathkul (2016)
Joint International Tropical Medicine Meeting 2001: Century Pard Hotel, Bangkok, Thailand 8-10 August 2001: abstract. Bangkok: Faculty of Tropical Medicine, Mahidol University; 2001. p.214